Anti-corrosion and anti-fouling properties of ball-like GQDs hybrided MOFs functionalized with silane in waterborne epoxy-polydimethylsiloxane coatings: Experimental and theoretical studies. (February 2023) - Zhou, Ziyang; Seif, Abdolvahab; Pourhashem, Sepideh; Duan, Jizhou; Rashidi, Alimorad; Mirzaee, Majid; Silvestrelli, Pier Luigi; Hou, Baorong
Highlights: Graphene quantum dots hybrided with ZIF-8 metal-organic framework (GQDs@MOF) is synthesized. GQDs@MOF is functionalized with 3-aminoproyltriethoxy silane (APTES) (i.e. F- GQDs@MOF). Epoxy modified by polydimethylsiloxane/APTES (EP-PDMS) is used as coating matrix. Nanocomposite EP-PDMS coatings loaded with 0.1 wt.% F-GQDs@MOF are prepared. EP-PDMS/F-GQDs@MOF coatings show superior corrosion and fouling resistance. Abstract: In this research, two strategies including epoxy matrix modification with 3-aminopropyltriethoxy silane (APTES) and polydimethylsiloxane (PDMS) as well as loading APTES-modified hybrids of graphene quantum dots and metal-organic framework (F-GQDs@MOF) are used to gain a composite epoxy coating with advance resistance against corrosion and fouling on Q235 steel structures. The X-ray analysis of diffraction and photoelectron spectroscopy, Fourier transform infrared spectroscopy, and morphology monitoring by transmission electron microscopy indicate that the GQDs are inserted inside the MOF structure through the in situ reaction, and the hybrid is successfully functionalized with the silane alkoxides. The EP-PDMS/F-GQDs@MOF composite coating shows high water contact angle (more than 100°), low surface roughness, high adhesion strength (8.5 MPa which is 2 times more than the EP-PDMS), superior electrochemical resistance (more than 10 8 Ω.cm 2 which is comparable with EP-PDMS sample with 10 6 Ω.cm 2 impedance modulus after immersion in the NaCl solution for 60 days), and negligible corrosion products and blisters after salt spray test. Moreover, the achieved data by the density functional theory (DFT) method show that the functionalization of the GQDs affects remarkably the strengthening of the interface between this moiety and the MOF in such a way to retard the electrochemical reactions. Besides, the results of immersion in Qingdao port reveal that negligible amounts of marine organisms have covered the surface of the EP-PDMS/F-GQDs@MOF sample, while Styela clava and Botrylloides sp. are attached on the EP-PDMS surface. The antibacterial activity of the EP-PDMS/F-GQDs@MOF against Pseudomonas sp. is proved by low attached bacteria on its surface. Graphical abstract: Image, graphical abstract